Harpagoside Protects Against Doxorubicin-Induced Cardiotoxicity via P53-Parkin-Mediated Mitophagy - Li, Weili; Wang, Xiaoping; Liu, Tianhua; Zhang, Qian; Cao, Jing; Jiang, Yanyan; Sun, Qianbin; Li, Chun; Wang, Wei; Wang, Yong (Frontiers in Cell and Developmental Biology, 2022)
Doxorubicin (DOX) is one of the most effective chemotherapeutic agents. However, its clinical use is limited due to the severe risk of cardiotoxicity. One of the hallmarks of doxorubicin-induced cardiotoxicity (DIC) is the cascade of mitophagy deficiency-mitochondrial oxidative injury-apoptosis, while so far, there is no preventive strategy for alleviating DIC by targeting this molecular mechanism. Excitedly, based on our previous drug screen in DIC zebrafish model, harpagoside (HAR) showed dramatic anti-DIC efficacy superior to dexrazoxane (DXZ) only cardioprotectant approved by FDA. Therefore, its pharmacological effects and molecular mechanism on DIC mouse and rat cardiomyocytes were further discussed. In vivo, HAR significantly improved cardiac function and myocardial structural lesions with concomitant of diminished mitochondrial oxidative damage and recovered mitophagy flux. In parallel, HAR protected mitophagy and mitochondria homeostasis, and repressed apoptosis in vitro. Intriguingly, both nutlin-3 (agonist of p53) and Parkin siRNA reversed these protective effects of HAR. Additional data, including fluorescence colocalization of Parkin and MitoTracker and mt-Keima for the detection of mitophagy flux and coimmunoprecipitation of p53 and Parkin, showed that HAR promoted Parkin translocation to mitochondria and substantially restored Parkin-mediated mitophagy by inhibiting the binding of p53 and Parkin. Importantly, the results of the cell viability demonstrated that cardioprotective effect of HAR did not interfere with anticancer effect of DOX on MCF-7 and HepG2 cells. Our research documented p53-Parkin-mediated cascade of mitophagy deficiency-mitochondrial dyshomeostasis-apoptosis as a pathogenic mechanism and druggable pathway and HAR as a cardioprotection on DIC by acting on novel interaction between p53 and Parkin.